Transmission of shocks to the Chinese economy in a global context: A model-based approach - Jeannine Bailliu; Patrick Blagrave (Bank of Canada, 2010)
To better understand the dynamics of the Chinese economy and its interaction with the global economy, the authors incorporate China into an existing model for the G-3 economies (i.e., the United States, the euro area, and Japan), paying particular attention to modelling the exchange rate and monetary policy in China. Their findings suggest that the Chinese economy adjusts more slowly to shocks, compared to the large advanced economies, because monetary policy is less effective and the real exchange rate more persistent. In addition, the authors' model underscores the importance of spillovers from China to the G-3 economies, and vice versa, thus highlighting the need to analyze the Chinese economy in a global context.
Keywords: E32; E52; F41; 330; Economic models; international topics; business fluctuations and cycles; exchange rate regimes; Globalisierung; Schock; Geldpolitik; Wechselkurspolitik; Wirtschaftslage; China; EU-Staaten; USA; Japan